The Influence of Communication and Organizational Commitment on The Work Achievement of Employees in Kantor Camat Beringin - Audilla Fahira (SEAN Institute, 2022)
Giving motivation is one of the methods used to increase the work productivity of the employees of the Beringin District Office. Failure to motivate them will result in not being able to carry out the work as desired by the employees of the Beringin Sub-district Office, this is due to their dissatisfaction at work. In carrying out motivation, it is important to pay attention to the circumstances and demands of the employees of the Beringin Head Office so that a motivation system can be established that can encourage work enthusiasm and sincerity of the workforce. Good working spirit will facilitate the achievement of company goals. Based on the description above, I am interested in compiling this research with the title